![\bf \begin{array}{llrrlllll} x+4y&=13&&x&+4y&=13\\ x-y&=3\implies \stackrel{\textit{multiplying this one by }}{-1}&&-x&+y&=-3\\ \cline{4-6}\\ &&&0x&+5y&=10 \end{array} \\\\\\ 5y=10\implies y = \cfrac{10}{2}\implies \boxed{y = 2} \\\\\\ \stackrel{\textit{since we know that}}{x-y=3}\implies x-(2)=3\implies \boxed{x = 5} \\\\[-0.35em] ~\dotfill\\\\ ~\hfill (\stackrel{x}{5}~~,~~\stackrel{y}{2})~\hfill](https://img.qammunity.org/2021/formulas/mathematics/middle-school/nsvaw3gmhooxbqum7q6davl6tgrq4iz6pm.png)
notice, is called the elimination method, because we eliminate one of the variables, either one, in this case the "x", by simply multiplying one of the equations by a value that gives us the negative equivalent of the other, and of course same - same = 0.